Circulating plasma concentrations of angiotensin-converting enzyme 2 in men and women with heart failure and effects of renin–angiotensin–aldosterone inhibitors. (10th May 2020) - Sama, Iziah E; Ravera, Alice; Santema, Bernadet T; van Goor, Harry; ter Maaten, Jozine M; Cleland, John G F; Rienstra, Michiel; Friedrich, Alex W; Samani, Nilesh J; Ng, Leong L; Dickstein, Kenneth; Lang, Chim C; et al.
Abstract: Aims: The current pandemic coronavirus SARS-CoV-2 infects a wide age group but predominantly elderly individuals, especially men and those with cardiovascular disease. Recent reports suggest an association with use of renin–angiotensin–aldosterone system (RAAS) inhibitors. Angiotensin-converting enzyme 2 (ACE2) is a functional receptor for coronaviruses. Higher ACE2 concentrations might lead to increased vulnerability to SARS-CoV-2 in patients on RAAS inhibitors. Methods and results: We measured ACE2 concentrations in 1485 men and 537 women with heart failure (index cohort). Results were validated in 1123 men and 575 women (validation cohort). The median age was 69 years for men and 75 years for women. The strongest predictor of elevated concentrations of ACE2 in both cohorts was male sex (estimate = 0.26, P < 0.001; and 0.19, P < 0.001, respectively). In the index cohort, use of ACE inhibitors, angiotensin receptor blockers (ARBs), or mineralocorticoid receptor antagonists (MRAs) was not an independent predictor of plasma ACE2. In the validation cohort, ACE inhibitor (estimate = –0.17, P = 0.002) and ARB use (estimate = –0.15, P = 0.03) were independent predictors of lower plasma ACE2, while use of an MRA (estimate = 0.11, P = 0.04) was an independent predictor of higher plasma ACE2 concentrations. Conclusion: In two independent cohorts of patients with heart failure, plasma concentrations of ACE2 were higher in men than in women, but use of neither an ACE inhibitor nor an ARB was associated with higher plasma ACE2 concentrations. These data might explain the higher incidence and fatality rate of COVID-19 in men, but do not support previous reports suggesting that ACE inhibitors or ARBs increase the vulnerability for COVID-19 through increased plasma ACE2 concentrations.